Eduard Lorenz Lorenz-Meyer. Ein Hamburger Kaufmann und Künstler - Gerhardt, Johannes (Mäzene für Wissenschaft, 2007)
The company Behn Meyer Deutschland Holding AG & Co. KG, headquartered at Ballindamm in Hamburg, is one of the most traditional trading houses in the Hanseatic city. Among other things, it sells rubber chemicals for the European market. In the company's history there have been a number of well-known personalities such as Arnold Otto Meyer and Franz Heinrich Witthoefft. Eduard Lorenz Lorenz-Meyer, who is one of the donors of the Hamburg Scientific Foundation, has always been somewhat in the shadows. However, if the focus is not primarily on economic aspects, but also on political and cultural aspects, a very multi-faceted life is evident.